THE EFFECT OF QUICK READING METHOD ON THE ABILITY OF SUMMARYING THE CONTENTS OF THE MODULE ON STUDENTS OF PGSD UPBJJ UT MEDAN - Muhammadi Muhammadi; Johannes Johannes; Hernawi Silalahi; Kula Ginting (SENSEI RESEARCH CENTER, 2022)
This study aims to determine how the ability of students of PGSD UPBJJ UT Medan to the ability to summarize the module by using the speed reading method. It is hoped that by using this speed reading method, students can easily summarize the contents of the module. The method used in this study is a quasi-experimental method with a research design of Pretest Posttest Control Group Design. This study took a sample of 14 experimental class students and 15 control class students. The instrument of this research is a description test which consists of 10 questions related to the ability to summarize the content of the module. Test validity is calculated by construct validity. To measure the validity of the construct can use the opinion of experts (Expert Judgment). After testing the hypothesis using the independent samples T-Test analysis technique, it was obtained that tcount was 0.021 at a significance level of <0.05. Thus H1 is accepted and H0 is rejected because 0.021 <0.05, so it can be concluded that there is an effect of using the speed reading method on the ability to summarize the contents of the module.